ACUTE AND SUBCHRONIC ORAL TOXICITY STUDIES OF ETHYL ACETATE EXTRACT OF SONCHUS ARVENSIS L. LEAVES - Nurianti, Yelvia
The plant Sonchus arvensis L., known in Indonesia as tempuyung, has been used widely as traditional drug. The most well-known activity of this plant is antikidney stone. Other uses of the plant include as diuretic agent, and amelioration of the impaired glucose tolerance. This plant has also been reported to have protective effect against CCl4-induced kidney damage in rat. Prior to human use, it is mandatory that a traditional drug should meet the safety requirement. Previous study showed that the ethyl acetate fraction of ethanol extract of Sonchus arvensis L. gave the highest activity in xanthine oxidase inhibition. In the present study acute oral toxicity and subchronic toxicity tests of ethyl acetate extract of Sonchus arvensis L. leaves were carried out to explore its safety feature. Extract was prepared by maceration in ethyl acetate. Acute oral toxicity test was conducted in ddY mice using the conventional method. Sixty mice were divided into 6 groups, namely control group and five test groups, each given the extract at 0.19 g/kg body weight (b.w), 0.56 g/kg b.w, 1.67 g/kg b.w, 5 g/kg b.w and 15 g/kg, respectively. Subchronic toxicity test was carried out in Wistar rats by daily administraion of ethyl acetate extract of Sonchus arvensis L. leaves for 90 days at 100 mg/kg b.w, 400 mg/kg b.w, and 1000 mg/kg b.w. The rats in all groups were observed for behaviour, body weight development, hematology, clinical biochemistry, organ to body weight ratio, and organ histology. No mortality was observed both in acute and subchronic toxicity tests in male and female animals. Observed behaviour, body weight profile and organ histology among experimental groups were comparable. Hematology, clinical biochemistry parameters, organ to body weight ratio were not significantly different.